1996
DOI: 10.1002/(sici)1096-9136(199610)13:10<908::aid-dia249>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Severe Ketoacidosis Complicated by ‘Ecstasy’ Ingestion and Prolonged Exercise

Abstract: Ecstasy (3,4‐methylenedioxymethamphetamine or MDMA) is used with increasing frequency as a recreational drug. Accumulated evidence over recent years indicates a growing demand for the drug with a corresponding increase in number of reports of adverse effects from its use. There are reported metabolic disturbances due to MDMA use. These, in addition to the prolonged exercise involved in dancing at ‘raves’ where MDMA may be used, may exacerbate ketoacidosis. We report two cases of ketoacidosis complicated by MDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Ecstasy and ketamine, particularly in combination, can result in marked hyponatraemia in ketoacidosis 2 , and serum sodium should be carefully monitored when concurrent drug use is suspected. Ketamine may cause agitation, hypertension, tachycardia and hyperthermia, with the danger of acidosis and rhabdomyolysis in severe intoxication 3 .…”
Section: Biochemistry Results On Admission To Emergency For Cases 1–3mentioning
confidence: 99%
“…Ecstasy and ketamine, particularly in combination, can result in marked hyponatraemia in ketoacidosis 2 , and serum sodium should be carefully monitored when concurrent drug use is suspected. Ketamine may cause agitation, hypertension, tachycardia and hyperthermia, with the danger of acidosis and rhabdomyolysis in severe intoxication 3 .…”
Section: Biochemistry Results On Admission To Emergency For Cases 1–3mentioning
confidence: 99%
“…A study in the United Kingdom indicated that street drug use in young adults with diabetes may contribute to poor glycemic control and serious complications of diabetes 24 . The metabolic disturbances such as diabetic ketoacidosis and poor glycemic control may be further exacerbated by MDMA abuse during prolonged exercise 25 …”
Section: Introductionmentioning
confidence: 99%
“…Both were insulin-dependent diabetics and ingested ecstasy during a rave party, during which they danced strenuously. They showed good clinical evolution after fluid replacement and the administration of insulin, although one of the patients developed bronchopneumonia and needed intubation and mechanical ventilation [11]. …”
Section: Discussionmentioning
confidence: 99%